OPTIMIZATION OF IMMOBILIZED ?-AMYLASE ON MODIFIED SILICA USING APTMS-GLUTARALDEHYDE AND NTMSPDETA-GLUTARALDEHYDE - Amanda, Priscilla
?-Amylase (E.C.3.2.1.1) is one of the most widely used enzymes in various industrial fields, such as the food, textile, pharmaceutical and chemical industries. The separation of ?-amylase from the reaction mixture, enzyme-substrate-product, is difficult to do so it causes limitations to the repeated use of the enzyme. Enzyme immobilization is an effective method to make enzymes reusable, thus lowering the costs required by industrial enzyme users. In addition, immobilization can also increase the stability of the enzyme. The purpose of this study was to analyze the immobilized performance of recombinant ?-amylase BmaN2 from Bacillus megaterium NL3 on modified silica matrix (3-aminopropyl)trimethoxysilane (APTMS)- glutaraldehyde and N1-[3-(trimethoxysilyl)propyl]diethylentriamine (NTMSPDETA)- glutaraldehyde by covalent binding method. In this study, silica was synthesized using tetraethyl orthosilicate (TEOS) and modified with APTMS or NTMSPDETA, and continued using glutaraldehyde. Based on the FTIR spectrum of APTMS modified silica and glutaraldehyde, the peak was obtained at the wave number 3737.47-3012.74 cm-1 which was obtained from the absorption of the O-H bond in the Si-OH group, the peaks at the wave numbers 1654.16 and 1630.8 cm-1 originating from the N-H group, the peak at wave number 1368.95-975.33 cm-1 belongs to the Si-O-Si group, and the peak at wave number 851.19- 754.77 cm-1 comes from the Si-O group. Whereas in the FTIR spectrum of modified silica NTMSPDETA and glutaraldehyde, the peak at wave number 3737.09-3005.39 cm-1 was obtained from the O-H bond absorption, the peak at wave numbers 1655.79 and 1629.06 cm-1 belonged to the N-H group, the peak at wave number 1367.67-975.73 cm-1 from the Si-O-Si bond absorption, the peak at wave number 850.28-755.9 cm-1 originating from the Si-O group absorption, and the peak at wave number 2995 cm-1 belongs to the C-H group. The color change of glutaraldehyde-modified silica from white to cream indicates that silica has been successfully modified. The performance test of APTMS modified silica and glutaraldehyde using the DNS method resulted in the optimum contact time of the matrix with the enzyme at 30 minutes, the optimum contacting temperature was 30 °C, the optimum pH of contacting was pH 4, the immobilized enzyme activity remained 41% after being used 4 times, and 39% remaining immobilized enzyme activity after 10 days of storage. Meanwhile, the performance tests for the modified silica NTMSPDETA and glutaraldehyde have not been carried out. Based on the results of research that has been done, enzyme immobilization has succeeded in changing the character of the enzyme and has the potential to be used repeatedly.